2019
DOI: 10.14202/vetworld.2019.205-210
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus isolated from selected dairies of Algeria: Prevalence and susceptibility to antibiotics

Abstract: Aim: The objectives of this study were to assess the prevalence of Staphylococcus aureus in raw milk in Algerian dairies, to study the effect of seasons on the contamination of milk and the susceptibility of isolated strains to antibiotics, and to estimate the risk on the health consumer. Materials and Methods: The ISO method 6888-1 (1) was used for Staphylococcus screening. Antimicrobial susceptibility to the 11most used antibiotics in veterinary medicine was assessed using the disk diffusion assay. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
8
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 25 publications
4
8
3
Order By: Relevance
“…With regards to animal-derived isolates, most strains showed resistance to penicillin (52%) and tetracycline (33%) in according with previous works [11,17,20,21,22,23]. By comparing our results with those obtained in a previous study [6] which reported the antimicrobial profile of 80 isolates collected between 1998–2014, we found an increase of resistance to penicillin (52% vs. 35.7%), tetracycline (33% vs. 20%), ceftriaxone (14% vs. 3.7%), and gentamicin (14% vs. 4%), which suggested the spread of resistance.…”
Section: Discussionsupporting
confidence: 83%
“…With regards to animal-derived isolates, most strains showed resistance to penicillin (52%) and tetracycline (33%) in according with previous works [11,17,20,21,22,23]. By comparing our results with those obtained in a previous study [6] which reported the antimicrobial profile of 80 isolates collected between 1998–2014, we found an increase of resistance to penicillin (52% vs. 35.7%), tetracycline (33% vs. 20%), ceftriaxone (14% vs. 3.7%), and gentamicin (14% vs. 4%), which suggested the spread of resistance.…”
Section: Discussionsupporting
confidence: 83%
“…For dairy product studies, in Algeria, similar results were reported, as described by [20,43,44]. In contrast, the prevalence obtained was higher than that found in Egypt (12%) [45], (16.60%) [23], Nigeria (9.15%) [46], China (1.8%) [22], Greece (18%) [27], Spain (7%) [26], and Italy (9.79%) [47] (11.77%) [29], with the highest prevalence registered in Georgia [12] and Turkey [48] with (63%) and (42.50%), respectively.…”
Section: Discussionsupporting
confidence: 82%
“…Chaalal et al [11] have reported a rate of 21.5% in various types of foods, including raw milk, meat, and pastries. Other studies conducted in Algeria have found a lower prevalence, with values of 4.1%−13.6% in raw milk and traditional dairy products [22][23][24], but, to the best of our knowledge, no study has examined goat milk.…”
Section: Discussionmentioning
confidence: 67%
“…Chaalal et al [11] have reported that 33.3% of the S. aureus strains mainly isolated from raw milk and raw meat were multi-drug resistant, with 45.7% resistant to one antibiotic and 20.0% sensitive to all the antibiotics tested [11]. Matallah et al [23] and Titouche et al [22] have reported that 3.15% and 23.18% of their strains were multi-resistant. Similar findings have been obtained in Italy [25] and Russia [35].…”
Section: Discussionmentioning
confidence: 99%